Geochemistry and isotopic ratios of boninites and related rocks of the Izu-Bonin Forearc - Julian A Pearce; Matthew F Thirlwall; Gerry Ingram; Bramley J Murton; Richard J Arculus; Sieger R van der Laan (PANGAEA, 1992)
Twenty-six samples representing the wide range of lithologies (low- and intermediate-Ca boninites and bronzite andesites, high-Ca boninites, basaltic andesites-rhyolites) drilled during Leg 125 at Sites 782 and 786 on the Izu-Bonin outer-arc high have been analyzed for Sr, Nd, and Pb isotopes. Nd-Sr isotope covariations show that most samples follow a trend parallel to a line from Pacific MORB mantle (PMM) to Pacific Volcanogenic sediment (PVS) but displaced slightly toward more radiogenic Sr. Pb isotope covariations show that all the Eocene-Oligocene samples plot along the Northern Hemisphere Reference Line, indicating little or no Pb derived from subducted pelagic sediment in their source. Two young basaltic andesite clasts within sediment do have a pelagic sediment signature but this may have been gained by alteration rather than subduction. In all isotopic projections, the samples form consistent groupings: the tholeiites from Site 782 and Hole 786A plot closest to PMM, the boninites and related rocks from Sites 786B plot closest to PVS, and the boninite lavas from Hole 786A and late boninitic dikes from Hole 786B occupy an intermediate position. Isotope-trace element covariations indicate that these isotopic variations can be explained by a three-component mixing model. One component (A) has the isotopic signature of PMM but is depleted in the more incompatible elements. It is interpreted as representing suboceanic mantle lithosphere. A second component (B) is relatively radiogenic (epsilon-Nd = ca 4-6; 206Pb/204Pb = ca 19.0-19.3; epsilon-Sr = ca -10 to -6)). Its trace element pattern has, among other characteristics, a high Zr/Sm ratio, which distinguishes it from the ìnormalî fluid components associated with subduction and hotspot activity. There are insufficient data at present to tie down its origin: probably it was either derived from subducted lithosphere or volcanogenic sediment fused in amphibolite facies; or it represents an asthenospheric melt component that has been fractionated by interaction with amphibole-bearing mantle. The third component (C) is characterized by high contents of Sr and high epsilon-Sr values and is interpreted as a subducted fluid component. The mixing line on a diagram of Zr/Sr against epsilon-Sr suggests that component C may have enriched the lithosphere (component A) before component B. These components may also be present on a regional basis but, if so, may not have had uniform compositions. Only the boninitic series from nearby Chichijima would require an additional, pelagic sediment component. In general, these results are consistent with models of subduction of ridges and young lithosphere during the change from a ridge-transform to subduction geometry at the initiation of subduction in the Western Pacific.
Supplement to: Pearce, JA et al. (1992): Isotopic evidence for the origin of Boninites and related rocks drilled in the Izu-Bonin (Osagawara) Forearc, Leg 125. In: Fryer, P; Pearce, JA; Stokking, LB; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 125, 237-261, https://doi.org/10.2973/odp.proc.sr.125.134.1992